Triggers of Inflammatory Heart Disease - Lasrado, Ninaad; Yalaka, Bharathi; Reddy, Jay (Frontiers in Cell and Developmental Biology, 2020)
Inflammatory heart disease (IHD) is a group of diseases that includes pericarditis, myocarditis, and endocarditis. Although males appear to be more commonly affected than females, IHD can be seen in any age group. While the disease can be self-limiting leading to full recovery, affected individuals can develop chronic disease, suggesting that identification of primary triggers is critical for successful therapies. Adding to this complexity, however, is the fact that IHD can be triggered by a variety of infectious and non-infectious causes that can also occur as secondary events to primary insults. In this review, we discuss the immunological insights into the development of IHD as well as a mechanistic understanding of the disease process in animal models.